Dietary and supplemental intake of one-carbon nutrients and the risk of type I and type II endometrial cancer: a prospective cohort study - Uccella, S. (Oxford University Press, 2011)
Background: Type I and II endometrial cancer are biologically and clinically distinct, with type II cancers having a high frequency of p53 mutations and an association with chromosomal instability. This raises the hypothesis that one-carbon nutrients (folate, methionine, and the enzymic cofactors vitamins B2, B6, and B12), which mediate chromosomal stability and DNA methylation, may be protective for type II but not type I endometrial cancer. Methods: Using a prospective cohort of 23 356 postmenopausal women followed 20 years, we estimated the relative risks (RRs) of type I (N = 471) and II (N = 71) endometrial cancers according to intake of one-carbon nutrients, adjusting for confounders. Results: No associations were observed between dietary or supplemental intake of any one-carbon nutrient and risk of type I cancer. For type II cancer, positive associations were due to supplemental, rather than dietary, intake of these nutrients: supplemental folate (RR = 1.80 for >228.6 versus 0 μg/day; P trend = 0.027) and vitamins B2 (RR = 1.94 for >1.70 versus 0 mg/day; P trend = 0.011), B6 (RR = 2.08 for >2.00 versus 0 mg/day; P trend = 0.012), and B12 (RR = 2.10 for >3.43 versus 0 μg/day; P trend = 0.0060). Conclusion: Contrary to our hypothesis, use of supplements containing folate and vitamins B2, B6, and B12 was associated with an increased risk of type II endometrial cancer.